Fourier method for solving the multi-frequency inverse source problem for the Helmholtz equation. (11th February 2015) - Zhang, Deyue; Guo, Yukun
Abstract: We consider an inverse source problem for the Helmholtz equation. This is concerned with the reconstruction of an unknown source from multi-frequency data obtained from the radiated fields. Based on a Fourier expansion of the source, a numerical method is proposed to solve the inverse problem. Stability is analyzed and numerical experiments are presented to show the effectiveness of our method.